Testing sample selection criteria and loss of biomarkers during cleaning of archaeological unglazed pottery to maximize organic residue quantities - Janzen, George; Formberg, Jason; Braun, Arno; Hammann, Simon; Hornung, Sabine; Fiedler, Sabine (Archaeometry, 2024)
As the number of studies in organic residue analysis (ORA) of ancient pottery—a sensitive but as of today also a destructive method—increases, archaeologists are interested in knowing which samples promise the biggest abundance of analytes in order to avoid unnecessary loss of artefacts. Another frequently asked question is whether the routinely performed cleaning procedure should be omitted for samples intended for ORA to preserve the availability of analytes. We tested several selection criteria commonly accessible to archaeologists (texture, position, shape) for lipid quantities in ancient pottery in order to determine the most productive sherds for analysis. Moreover, we monitored loss of lipids during the water-and-brush cleaning process. Beside the usually targeted straight-chain fatty acids (FA), less abundant biomarkers such as α,ω-dicarboxylic acids (DCA), ω-(o-alkylphenyl)alkanoic acids (APAA) and hydroxy fatty acids (HFA) were also screened. The highest concentrations of analytes were observed in rims of coarse-textured plates and cooking pots, demonstrating the usefulness of the proposed criteria. The washing procedure applied here did not lead to a loss of bulk FA, although the effect on minor components was not uniform.
CRIS-Team Scopus Importer:2024-08-16
Keywords: ancient pottery; archaeological science; fatty acid methyl esters; GC-MS; hydroxy fatty acids; α; ω-dicarboxylic acids; ω-(o-alkylphenyl)alkanoic acids